Relationship of Dysmenorrhea and Physical Activity with Anxiety - Een Sumarni; M.Pemberdi Intasir (Universitas Andalas, 2022)
This study aims to determine the relationship between dysmenorrhea and physical activity with anxiety. The method used in this study is a cross sectional study. A sample of 46 biology education students class of 2021 FKIP UMRAH used a total sampling technique. The Wong Boker Pain Face was used to measure dysmenorrhea pain, the IPAQ (International Physical Activity Questionnaire ) questionnaire measured physical activity and the BAI (Beck Anxiety Inventory) questionnaire measured anxiety. Data analysis using Chi Square. The results of data analysis of dysmenorrhea with anxiety showed a p value of 0.01 (p<0.01) and the results of data analysis of physical activity with anxiety showed a p value of 0.06 (p>0.06). Thus it can be concluded that there is a significant relationship between dysmenorrhea and student anxiety and there is no significant relationship between physical activity and anxiety.